Decostruzione delle figure maschili nella narrativa dei “giovani narratori” della fine del Novecento - Kornacka, Barbara (Romanica Silesiana)
The Deconstruction of Male Figures in the “Young Writers”’ Fiction of the End of Twentieth Century The aim of the article is to present the image of male protagonists in the literature written by some of so-called “young writers” of the 80s and 90s in Italy. These authors deprive the male figure of his traditional attributes of authority and power. They achieve this aim by realizing textual strategies such as a metaphorical attempt on the patriarch or an attack on other’s male authority, by a visualization of the masculinity as uncompleted or prosthetic, and by a victimization of the male protagonist. Key words: Italian literature of the 80s and 90s, male protagonist, crisis.